2020
DOI: 10.24071/ijiet.v4i2.2344
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' Views on the Integration of Technology in Efl Classroom

Abstract: In many study results, technology integration has been indicated to contribute regularly on the development of students 21st century skills ultimately in this digital era. This condition particularly creates new challenges for language teachers, e.g. being digitally literate, being adaptable with rapid technological changes, finding alternatives to stimulate the students to learn, and creating conducive class atmosphere. Considering previous points, this paper presents teachers view on the integration of techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…For this, English teachers need to help maintain good relations with EFL and ESL learners, encourage them to use English more often, and create classroom activities in order to enhance more student interactions. Third, regarding the importance of integrating technology in a language classroom, as suggested by Tanjung (2020), teachers are highly demanded to put great concern into selecting, preparing, integrating, assessing, and evaluating types of technology being employed in classroom instruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this, English teachers need to help maintain good relations with EFL and ESL learners, encourage them to use English more often, and create classroom activities in order to enhance more student interactions. Third, regarding the importance of integrating technology in a language classroom, as suggested by Tanjung (2020), teachers are highly demanded to put great concern into selecting, preparing, integrating, assessing, and evaluating types of technology being employed in classroom instruction.…”
Section: Discussionmentioning
confidence: 99%
“…With the fast development of technology, there has been an extensive search for how it is integrated into language teaching. A number of studies have pointed out that the use of technology in the language classroom allows teachers to provide interactive and meaningful activities which can engage students to actively participate in the class (Tanjung, 2020). Besides, Anggeraini (2018) also confirmed that the integration of technology plays an important role in promoting interactive learning and teaching activities as well as enhancing learners' initiatives to learn and be more creative learners.…”
Section: The Use Of English In Classroommentioning
confidence: 99%
“…According to Mollaei and Riasati (2013), with the fast growth of technology in all dimensions of our life, including in the field of education, teachers and students control their learning process and conduct online classes using technology as a tool to enhance their education. The development of technology has set education in high demand for a reform on its pedagogical approach (Tanjung, 2020). Moreover, students' preference to learn has changed dramatically since the introduction of the internet (Hartman, Townsend, & Jackson, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Natural science, commonly known as science, is a crucial area of knowledge and skill development that must be cultivated in elementary education (Fitria et al, 2021;Kafah et al, 2020). The impact of the rapid advancement of information technology in the contemporary era of globalization on education is an inescapable reality (Sun & Chen, 2016;Tanjung, 2020). The natural sciences and technologies of this world have seen a great deal of change, which may be observed from the way in which the environment affects our daily life (Lampropoulos et al, 2019;Zulfadewina et al, 2020).…”
Section: Introductionmentioning
confidence: 99%